In vivo and in vitro assessment of the biocompatibility and degradation of high-purity Mg anastomotic staples. (March 2017) - Qu, Su; Xia, Jiazeng; Yan, Jun; Wu, Hongliu; Wang, Hao; Yi, Yi; Zhang, Xiaonong; Zhang, Shaoxiang; Zhao, ChangLi; Chen, Yigang
Titanium (Ti) staples are not biodegradable, and anastomotic complications related to Ti staples are reported frequently. In the present study, the biocompatibility and degradation behavior of high-purity magnesium (HP Mg) staples with the small intestine were investigated. HP Mg staples did not affect the relative growth rate, cell cycle and apoptosis of primary rectal mucosal epithelial cells (IEC-6) in vitro . At one, two and three days after immersion in intestinal juice, the weight of the 30 rinsed HP Mg staples reduced by 7.5 ± 1.6, 10.6 ± 2.2 and 13.5 ± 2.1 mg, respectively, and those in the Hanks' solution reduced by 3.9 ± 0.8, 6.1 ± 1.2 and 7.1 ± 2.4 mg. Extracts of HP Mg staples were bio-safe for IEC-6, and the corrosion rate of HP staples was faster in the small intestinal juice than in the Hanks' solution. In the in vivo experiments, the small intestine of the minipigs was anastomosed by HP Mg and Ti staples. HP Mg staples neither affected important bio-chemical parameters nor induced serious inflammation or necrosis in the anastomosis tissues. The residual weight of a HP Mg staples (0.81 ± 0.13 mg) was 89.7% of the original weight (9 ± 0.09 mg) one month after surgery. The in vivo corrosion rate for one HP Mg staple was determined to be∼0.007 ± 0.001 mm·month −1 . The preliminary results of the biocompatibility and degradation of high-purity Mg anastomotic staples are promising, and further studies will be initiated to study in more detail.